Trees and Fields and Negative Polarity - Vikner, Sten (HERMES - Journal of Language and Communication in Business, 2011)
The paper takes as its point of departure a comparison between two kinds of approaches to clause structure, namely tree analyses like the generative analysis and ﬁeld analyses like the sætningsskema analysis of Danish of Diderichsen (1946) and many others (or like the topologische Modell analysis of German of Drach 1937 and many others). The particular difference between the two kinds of analyses which I explore in this paper concerns c-command, which is a relationship between different constituents in a clause. I shall try to show how useful and indispensable c-command is when it comes to accounting for negative polarity items in English, Danish and German, both the more straightforward aspects and the more complex ones, e.g. the so-called NPI-verbs as well as the interaction between NPI-elements and because-clauses.